Sex Workers in Canada Face Unequal Access to Healthcare: A Systems Thinking Approach - Kaitlyn Squires (SAGE Publishing, 2024)
Objectives: Despite Canada's universal health system, sex workers across the country face an alarmingly high number of barriers when they seek to healthcare services. This has resulted in unmet healthcare needs and substantially poorer health outcomes than the general Canadian population. The objective of this study was to use a systems thinking approach to gain an in-depth understanding of the barriers sex workers face and how access could be improved. Methods: The analysis was conducted using a systems thinking methodology, which incorporates systems tools and inquiry processes. The methodology comprised 2 domains of inquiry: (1) Problem Landscape, (2) Solutions Landscape. Systems tools and methods, such as causal loop diagrams, iceberg diagram, and systems mapping, investigated the problem landscape for understanding the interconnected nature of the issue, alongside review of both published and gray literature. An environmental scan explored the current solutions landscape. These methods connected through systemic inquiry processes, including ongoing review and application of diverse perspectives, boundary judgments, interrelationships; enabled gaps and levers of change to be determined. Results: The main barriers sex workers face are stigma, criminalization, accessibility, and cost of healthcare. The stigma of sex work stems from otherization, paternalism, and moralistic, faith-based beliefs. The barriers unique to sex work are stigma and criminalization; both of which surface as avoidance, dislike, and/or fear of medical professionals. Five gaps each with a lever of change to improve access were identified: (1) Stigma - Collectivization and external collaboration, (2) Criminal status of sex work - Decriminalization, (3) Lack of adequate education - Improved healthcare professional training and anti-discriminatory health policies, (4) Lack of support - Increased community-based healthcare services, (5) Cost of healthcare - Universal coverage of "secondary" healthcare components. Conclusion: Through reducing the stigma surrounding sex work, making changes that improve the healthcare services that sex workers receive, and collaboration between involved parties, sex workers can be prevented from falling through the cracks of the Canadian healthcare system; lessening the health inequities sex workers face and improving their health outcomes.